Optical coherence tomography and electroretinography in pituitary macroadenomas: a 12-month analysis by age and tumor type - Sarnat-Kucharczyk, Monika; Janik, Małgorzata A.; Janik, Paweł; Kos-Kudła, Beata; Pojda-Wilczek, Dorota (Frontiers in Endocrinology, 2025)
PurposeTo evaluate longitudinal changes in optical coherence tomography (OCT) and electroretinography (ERG) parameters over 12 months in patients with pituitary macroadenomas, and to assess variation according to age and tumor type.MethodsThis prospective observational study included 36 patients (72 eyes) with newly diagnosed pituitary macroadenomas. Patients were divided into a treatment group (n=23; including 9 prolactinomas (PRL), and 14 non-functioning adenomas [NFPAs]) and an observation group (n=13; all NFPAs). Both groups were further stratified by age (<60 vs. ≥60 years). Retinal nerve fiber layer (RNFL) and ganglion cell–inner plexiform layer (GCIPL) thickness was measured by OCT, while functional assessment included photopic negative response (PhNR) amplitude and W-ratio from full-field ERG. Measurements were performed at baseline and 12 months. Comparative and correlation analyses evaluated longitudinal, age-, and tumor-related differences.ResultsMean age did not differ between groups (treatment: 57.4 ± 13.0 years; observation: 54.9 ± 17.2). GCIPL thickness showed no consistent group differences, except temporal thinning in observation patients ≥60 years. RNFL thinning was significant in treated patients ≥60 years (average and inferior/temporal quadrants) and in younger treated patients (<60 years) in the superior and nasal quadrants. Observation patients <60 years showed RNFL loss in average and superior values, whereas no significant RNFL changes occurred in those ≥60 years. PhNR amplitude decreased in treated patients ≥60 years, while W-ratio increased in both treated subgroups and in younger observation patients. Strong structure–function correlations were observed in treated patients ≥60 years, particularly between GCIPL average and PhNR amplitude (R=–0.51) and RNFL superior and PhNR amplitude (R=–0.63).ConclusionsStructural and functional retinal parameters (GCIPL, RNFL, PhNR) may provide supportive information for monitoring visual pathway involvement in pituitary macroadenomas. Differences between PRL and NFPAs were more evident in treated NFPA patients <60 years, suggesting tumor type and age may influence biomarker sensitivity. The absence of such differences in older patients may reflect biological homogeneity or reduced responsiveness of retinal structures. Age should be considered a potential modifier when interpreting OCT and ERG findings across clinical phenotypes of pituitary macroadenomas.